2008
DOI: 10.1007/978-0-387-69080-3_55
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Androgen Regulation of ZEB-1 and PSA in 22RV1 Prostate Cancer Cells

Abstract: Two-thirds of patients who present with metastatic prostate cancer (PC) are dead within 5 years of diagnosis. The comparable survival rate for patients with localized disease is 100%, which clearly stresses the need for pursuing and developing bioassays that allow prediction of which localized cases are most likely to metastasize. The commonly assayed prostate specific antigen (PSA), while touted as a transformation biomarker, has recently proven to be problematic in the area of false positive diagnoses. It re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
5
12
2
Order By: Relevance
“…More importantly, our data showed that down-regulation of ZEB1 gene expression correlated with poor overall survival (P = .011) and diseasefree survival (P = .053). These results are surprising, because ZEB1 expression has been suggested as a biomarker of metastasis in a prostate cancer cell line and related with androgen regulation [25]. However, it is also possible that our samples represent tumors in which E-cadherin expression is temporarily lost, allowing tumor cells to migrate.…”
Section: Discussionmentioning
confidence: 47%
“…More importantly, our data showed that down-regulation of ZEB1 gene expression correlated with poor overall survival (P = .011) and diseasefree survival (P = .053). These results are surprising, because ZEB1 expression has been suggested as a biomarker of metastasis in a prostate cancer cell line and related with androgen regulation [25]. However, it is also possible that our samples represent tumors in which E-cadherin expression is temporarily lost, allowing tumor cells to migrate.…”
Section: Discussionmentioning
confidence: 47%
“…Slug and Zeb1 are well-known transcription factors downstream of TGFβ and Twist and there is a plethora of literature relating the role of Slug in EMT, cell proliferation and invasiveness of metastatic PCa cell lines [15, 41, 48]. Zeb1 expression is seen in highly aggressive PCa cells and correlates directly with Gleason grade in human prostate tumors [1]. Additionally, the reversal of the EMT phenotype in PC3 cells has been associated with the down-regulation of ZEB1, ZEB2, and SLUG [11, 12].…”
Section: Resultsmentioning
confidence: 99%
“…In human cancers, high ZEB1 expression correlated significantly with a high Gleason score in prostate carcinomas and was suggested as biomarker for metastasis [140,150].…”
Section: Zeb1 In Cancermentioning
confidence: 99%